The trade-off between child quantity and child quality and the public provision of education: A case study in rural Terengganu, Malaysia - Abdul Razak, Nor Azam; Abdul Hakim, Roslan; Ismail, Russayani (Universiti Utara Malaysia, 2010)
The objective of this paper is to examine whether the theory of the child quantity-quality (CQQ) trade-off developed by Becker and Lewis (1973) is borne out by the data from a developing country.In brief, the theory states that households behave differently with respect to their mixture of child quantity and child quality depending on their standards of living (i.e. low-income households tend to choose child quantity at the expense of child quality, and the converse is true for high-income households).If the government provides enough support for education, however, this trade-off might be undermined.Using a sample of 885 children from a survey of 2,500 households in rural areas in Terengganu in 2009, we conducted an empirical analysis on the relationship between child quantity and child quality.In the baseline estimation as well as in a series of robustness check, our key findings are that there is a positive yet insignificant impact of child quantity on child quality.Accordingly, we take these results as mild evidence against the CQQ trade-off which, in turn, can be attributed to the magnitude of the public provision of education in Malaysia.